2014
DOI: 10.7314/apjcp.2014.15.6.2911
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Sensitizes Two Oxaliplatin-Resistant Colorectal Cancer Cell Lines to Chemotherapeutic Drugs Via Inhibition of the Nrf2 Pathway

Abstract: Oxaliplatin is a first-line therapy for colorectal cancer, but cancer cell resistance to the drug compromises its efficacy. To explore mechanisms of drug resistance, we treated colorectal cancer cells (HCT116 and SW620) long-term with oxaliplatin and established stable oxaliplatin-resistant lines (HCT116-OX and SW620-OX). Compared with parental cell lines, IC 50 s for various chemotherapeutic agents (oxaliplatin, cisplatin and doxorubicin) were increased in oxaliplatin-resistant cell lines and this was accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 26 publications
3
59
0
Order By: Relevance
“…Luteolin is reported to activate the Nrf2 in AOM-induced colon cancer (Pandurangan et al, 2014a). On the other hand luteolin sensitizes two oxaliplatin-resistant colorectal cancer cell lines to chemotherapeutic drugs via inhibition of the nrf2 pathway (Chian et al, 2014). This phenomenon was further confirmed by the elevated expression of GST-α and GST-µ (Summart et al, 2014).…”
Section: Luteolin Effects On the Nrf2/keap1 Pathwaymentioning
confidence: 77%
“…Luteolin is reported to activate the Nrf2 in AOM-induced colon cancer (Pandurangan et al, 2014a). On the other hand luteolin sensitizes two oxaliplatin-resistant colorectal cancer cell lines to chemotherapeutic drugs via inhibition of the nrf2 pathway (Chian et al, 2014). This phenomenon was further confirmed by the elevated expression of GST-α and GST-µ (Summart et al, 2014).…”
Section: Luteolin Effects On the Nrf2/keap1 Pathwaymentioning
confidence: 77%
“…Luteolin, also known as 3',4',5',7'-tetrahydroxyflavone, is a flavonoid compound that has a C6-C3-C6 structure and possesses two benzene rings, an oxygen-containing ring and a 2-3 carbon double bond. This compound has been Luteolin, a novel p90 ribosomal S6 kinase inhibitor, suppresses proliferation and migration in leukemia cells LAN found to possess various beneficial properties, including antioxidant (11), anti-inflammatory (12), anti-bacterial (13) and anti-cancer activities (14)(15)(16)(17). Recently, Reipas et al (18) reported that luteolin is a novel p90 RSK inhibitor that can be considered as a promising candidate agent for the treatment of liver, lung, breast, colon, prostate, gastric and ovarian cancer, as well as melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have showed that luteolin play an important role in prevention of the human body against inflammation, reactive oxygen species and cancer. Luteolin can inhibit Nrf2 signaling activation in drug-resistant cells and suppress expression of Nrf2-targeted genes in small intestinal cells of wild type mice, but had no significant effects in knockout mice (Chian et al, 2014). Furthermore, luteolin decreased activity of mitochondrial enzyme significantly in mice with colon cancer induced with Azoxymethane (Pandurangan et al, 2012).…”
Section: Discussionmentioning
confidence: 98%